2020
DOI: 10.1007/s00266-020-01666-6
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue in Multiple Symmetric Lipomatosis Shows Features of Brown/Beige Fat

Abstract: Introduction Multiple symmetric lipomatosis (MSL) (syn.: Launois-Bensaude Syndrome, benign symmetric lipomatosis) is a rare disease of fatty tissue. The pathophysiology of MSL still remains unclear, although several approaches have been described in order to understand it. Beside morphological characteristics and some molecular cell biological approaches, little is known about the histological and immunohistochemical characterization of adipose tissue from patients with MSL. Methods From the 45 patients with M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Preliminary studies considered LT as a BAT depot, defective of brown adipogenic differentiation, on the basis of its anatomical localization and UCP1 expression [3,9,13,27], despite the fact that the majority of LT histologies showed the presence of typical white adipocytes [28,29], and gene expression data were often contrasting [10,13,30,31]. Our histological analyses clearly showed that LT displays a typical white AT morphology with mature and univacuolated adipocytes, differently from the multivacuolated adipocytes of the positive browning controls.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Preliminary studies considered LT as a BAT depot, defective of brown adipogenic differentiation, on the basis of its anatomical localization and UCP1 expression [3,9,13,27], despite the fact that the majority of LT histologies showed the presence of typical white adipocytes [28,29], and gene expression data were often contrasting [10,13,30,31]. Our histological analyses clearly showed that LT displays a typical white AT morphology with mature and univacuolated adipocytes, differently from the multivacuolated adipocytes of the positive browning controls.…”
Section: Discussionmentioning
confidence: 74%
“…Preliminary studies considered LT as a BAT depot, defective of brown adipogenic differentiation, on the basis of its anatomical localization and UCP1 expression [3,9,13,27], despite the fact that the majority of LT histologies showed the presence of typical white adipocytes [28,29], and gene expression data were often contrasting [10,13,30,31]. Our histological analyses clearly showed A,B) Representative photomicrographs (20× magnification) of nonproliferating vs. proliferating (cell confluence) and nonadipogenic vs. adipogenic (adipogenesis > 20%) wells counted to determine, respectively, the clonogenic and adipogenic potential of LT precursor cells derived from MSL patient 2891 I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several studies tried to elucidate the biology underneath the pathology without reaching a definitive conclusion [5,6]. In fact, it has been reported that MD tissues and cells show aberrant growth, mitochondrial energy metabolism, brown fat tissue alterations, and adipogenic index, ascribing these phenomena to specific proteins, such as Uncoupling Protein (UCP)-1 (a brown adipocyte marker) [7,8], calcyphosine-like (CAPSL) protein [9], or microRNAs such as miR-125a-3p and miR-483-5p, all associated with adipogenesis or fatty acid oxidation in peroxisomes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Level of Evidence V This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Thank you very much for your thoughts on this study [1]. The hematoxylin-eosin staining of affected and unaffected fatty tissue in patients suffering from MSL showed increased inflammatory infiltration as compared to control fatty tissue of healthy patients.…”
mentioning
confidence: 96%